2012
DOI: 10.1002/jcu.21896
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis of fetal intestinal volvulus with ileal atresia: A case report

Abstract: Fetal intestinal volvulus is a rare life-threatening condition usually manifesting after birth with most cases being associated with intestinal malrotation. It appears on prenatal sonography (US) as a twisting of the bowel loops around the mesenteric artery, leading to mechanical obstruction and ischemic necrosis of the bowel. We report a case of intrauterine intestinal volvulus with ileal atresia, suspected when US revealed a typical "whirlpool" sign at 37 weeks' gestation, with a segment of markedly distende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 10 publications
1
26
0
2
Order By: Relevance
“…In fact, intestinal atresia can develop after or before the volvulus. On one hand, as stated above and consistent with Yu et al (2013), atresia can result from intrauterine volvulus causing ischaemia followed by atresia of the associated intestine. On the other hand, Ogunyemi (2000) showed that ileal atresia could possibly occur first and therefore, increased peristalsis in the dilated intestine before the atresia could result in volvulus.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…In fact, intestinal atresia can develop after or before the volvulus. On one hand, as stated above and consistent with Yu et al (2013), atresia can result from intrauterine volvulus causing ischaemia followed by atresia of the associated intestine. On the other hand, Ogunyemi (2000) showed that ileal atresia could possibly occur first and therefore, increased peristalsis in the dilated intestine before the atresia could result in volvulus.…”
supporting
confidence: 53%
“…It may cause complications or lesions including vascular obstruction, congestion, haemorrhage, ischaemic injury and infarction (Gelberg, 2012). Intestinal atresia in approximately 25% of cases is followed by intestinal volvulus (Ogunyemi, 2000;Yu et al, 2013). Here, we present congenital type II terminal ileal atresia with the absence of the ileocaecal valve and volvulus of the ileum and the terminal part of the jejunum in a newborn goat.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Volvulus is frequently associated with atresia of the small intestine, which can be the cause or the mechanical consequence of midgut volvulus . In our series, for the cases diagnosed at the earliest stage, volvulus was clearly shown without any evident or substantial intestinal dilatation.…”
Section: Discussionmentioning
confidence: 70%
“…Various etiologies for intestinal volvulus have been described in infants alive in the neonatal period, including meconium peritonitis and intestinal mesentery defects 1718. Pathognomonic sonographic findings in the third trimester ultrasound examination, such as the whirlpool sign, aids in rapid antenatal diagnosis of intestinal volvulus 192021. Characteristics of these cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%